Toward Sustainable Innovation: A Participatory Study on Designers’ Tool Needs for Circular Product Design - Lam, Hio Kuan; Chang, Wan-Ling; Hsu, Ting-Yu (European Journal of Sustainable Development, 2025)
The circular economy (CE) provides a framework for sustainable production and consumption, with circular design playing a critical role in shifting from linear systems to models that promote continuous reuse of materials and products. However, many existing design tools focus on high-level strategies that assume entirely new business models, making them less applicable to production-oriented industries. This study explores the practical needs of designers in developing tools that support early-stage circular product ideation, where the majority of a product’s sustainability impacts are determined. We conducted two co-design workshops using a participatory design approach to surface user needs and assess current tools. Participants were graduate students in industrial design with foundational CE knowledge and experience in circular design projects. In the first workshop, participants tackled rapid design challenges and evaluated the usability and limitations of existing tools. In the second, researchers introduced key CE frameworks — such as the butterfly diagram, 9R framework, and Design for X (DfX) strategies — which participants used to prototype a circular product design card tool. The study reveals specific, practice-based needs that can guide the development of user-centred circular design tools. These insights offer a foundation for creating more actionable, production-aligned resources to support CE transitions. Keywords: Circular Economy, Circular Product Design, New Product Development, Product Circularity, Design for X(DfX), Design Strategy